Versican V1 in human endometrial epithelial cells promotes BeWo spheroid adhesion in vitro. Issue 1 (January 2019) - Miyazaki, Yumiko; Horie, Akihito; Tani, Hirohiko; Ueda, Masashi; Okunomiya, Asuka; Suginami, Koh; Kondoh, Eiji; Baba, Tsukasa; Konishi, Ikuo; Shinomura, Tamayuki; Sato, Yukiyasu
Abstract : The endometrium extracellular matrix (ECM) is essential for embryo implantation. Versican, a large chondroitin sulfate proteoglycan that binds hyaluronan and forms large ECM aggregates, can influence fundamental physiological phenomena, such as cell proliferation, adhesion and migration. The present study investigated the possible role of versican in human embryo implantation. Versican V1 expression and secretion in human endometrial epithelial cells (EECs) was most prominent in the mid-secretory phase. Versican expression in EECs significantly increased after treatment with estrogen and progesterone, but not by estrogen alone. We also established versican V1-overexpressing Ishikawa (endometrial cancer cell line) cells (ISKW-V1), versican V3-overexpressing (ISKW-V3) and control GFP-overexpressing (ISKW-GFP) Ishikawa cells. By the in vitro implantation model, the attachment ratio of BeWo (choriocarcinoma cell line) spheroids to the monolayer of ISKW-V1, but not of ISKW-V3, was found significantly enhanced compared with attachment to the ISKW-GFP monolayer. The conditioned medium derived from ISKW-V1 (V1-CM) also promoted the attachment of BeWo spheroids to the ISKW monolayer. However, this attachment-promoting effect was abolished when V1-CM was pretreated with chondroitinase ABC, which degrades chondroitin sulfate. Therefore, out of the ECM components, versican V1 may facilitate human embryo implantation.